Nuclear medicine board review : questions and answers for self-assessment - Goldfarb, C. Richard; Chamarthy, Murthy R.; Ongseng, Fukiat (Thieme, 2018)
Nuclear Medicine Board Review: Questions and Answers for Self-Assessment, 4th Edition mirrors cutting-edge advances in this key field. Authored by C. Richard Goldfarb and expert colleagues, the interactive question-and-answer format is designed to speed assimilation of relevant information and facilitate retention. Twenty-four chapters encompass 2,250 questions enhanced with high-quality images and a wide range of question formats, including multiple-choice, matching test, and true/false. This book provides a robust review for certifying exams administered by the American Board of Radiology, t.